2021
DOI: 10.34067/kid.0002792020
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Sox6 Controls Renin Expression during Renal Artery Stenosis

Abstract: Background: Renal artery stenosis (RAStenosis) or renal artery occlusion is an intractable problem affecting about 6% of people over 65 and up to 40% of the people with coronary or peripheral vascular disease in the Unites States. In RAStenosis, the renal renin angiotensin aldosterone system (RAAS) plays a key role, with renin recognized as the disease driver. Renin is mainly produced in the kidney and in this study, we will determine a new function for the transcription factor Sox6 in the control of renal ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Blood pressure measurement. Blood pressure measurements were performed using a tail-cuff method following previously reported recommendation for precise measurements previously reported 15 . Blood pressure was also measured 4 weeks after Ang II infusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood pressure measurement. Blood pressure measurements were performed using a tail-cuff method following previously reported recommendation for precise measurements previously reported 15 . Blood pressure was also measured 4 weeks after Ang II infusion.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously found that Sox6 has a function as a regulator of renin expression controlling the rate limiting step in RAAS 15,16 . Knocking out Sox6 in Ren1d+ cells inhibited renal artery stenosis induced hypertension and kidney injury 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stimulation triggers a series of events starting with renin release leading to angiotensin II (Ang II) production, decrease in sodium excretion, increase sympathetic tone; all contributing to the development of hypertension (Figure 1) [17,18]. When there is a need for renin expression and release, the number of renin expressing cells increase a process known as Juxtaglomerular (JG) cell recruitment [19][20][21][22][23][24] involving the trans differentiation of vascular smooth muscle cells into renin expressing cells along the afferent arteriole [20,21,23]. JG cell recruitment is well documented in this model [25][26][27].…”
Section: Renin Angiotensin Aldosterone System Function In Renal Artery Stenosismentioning
confidence: 99%
“…RAS is common in atherosclerotic patients and caused hypertension, oxidative stress, and kidney damage [7,9]. Increased oxidative stress has been reported in humans as well as in two kidney one clip (2K1C) animal model and other hypertensive animal models [24,[55][56][57][58][59][60]. Changes in renal perfusion activate RAAS and increase the sympathetic activity of the afferent renal nerves contributing to renovascular hypertension and end-stage renal disease during RAS [61].…”
Section: Renin Angiotensin Aldosterone System Function In Renal Artery Stenosismentioning
confidence: 99%